Filsafat Hedonisme Epikuros: Sebagai Refleksi Bagi Remaja Kristen - Irwan Heruadi; Resnita Resnita; Ikbal Saogo; Aldo Master; Junardi Sihaloho (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Gradual changes in time change the perspective and behavior of human life. The development of global capitalism and consumer culture has led individuals or teenagers to a style of hedonism that is oriented towards materialistic concepts or pleasure because of material things. This research uses qualitative methods with a literature study approach. The result of this discussion is that contemporary era hedonism is very different from Epicurean hedonism. Hedonism in Epicurus' view is oriented towards spiritual pleasure as a balance to material pleasure. Christian teenagers who orient themselves towards contemporary hedonism will enter the area of ​​attachment, while teenagers who self-reflect and pursue spiritual pleasure will be free from attachment, living in happiness in simplicity.